2006
DOI: 10.1007/s10533-006-9024-8
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Transformation in a Nitrogen-Rich Tidal Freshwater Marsh

Abstract: The fate and transport of watershedderived ammonium in a tidal freshwater marsh fringing the nutrient rich Scheldt River, Belgium, was quantified in a whole ecosystem 15 N labeling experiment. In late summer (September) we added 15 N-NH 4 + to the flood water entering a 3477 m 2 tidal freshwater marsh area, and traced the ammonium processing and retention in four subsequent tide cycles. In this paper we present the results for the water-phase components of the marsh system and compare them to a similar experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The marshes and bays could export dissolved Si and import NO − 3 (Cai et al, 2000;Gribsholt et al, 2006;Das et al, 2010), and thus could show high Si : NO − 3 ratios in the waters from the marshes (Ren et al, 2009;Struyf et al, 2011) in contrast to a low Si : NO − 3 ratio (≈ 1) from the Mississippi River (Turner and Rabalais, 2004;Lohrenz et al, 1999). We found that shelf waters close to Barataria Bay had high Si concentrations and low NO − 3 concentrations, especially in June 2003 (Figs.…”
Section: The Role Of Salt Marshes and Baysmentioning
confidence: 71%
“…The marshes and bays could export dissolved Si and import NO − 3 (Cai et al, 2000;Gribsholt et al, 2006;Das et al, 2010), and thus could show high Si : NO − 3 ratios in the waters from the marshes (Ren et al, 2009;Struyf et al, 2011) in contrast to a low Si : NO − 3 ratio (≈ 1) from the Mississippi River (Turner and Rabalais, 2004;Lohrenz et al, 1999). We found that shelf waters close to Barataria Bay had high Si concentrations and low NO − 3 concentrations, especially in June 2003 (Figs.…”
Section: The Role Of Salt Marshes and Baysmentioning
confidence: 71%
“…The higher degree of labelling in September compared to May was due to a combination of significantly lower ammonium concentrations in the flood water (Fig. 2a) and lower tidal height (see Discussion; Gribsholt et al, 2006). Thus only half the volume of water flooded the marsh during September labelling compared to May ( Table 2).…”
Section: Isotopic Labellingmentioning
confidence: 88%
“…To maximize contrasts we therefore scheduled our two experiments in spring (May), when plants were young and building up biomass, and late summer (September), when macrophytes were in a flowering or early senescent state, respectively. The detailed results of the water-phase component of these studies have been described previously (Gribsholt et al, 2005(Gribsholt et al, , 2006. In both May and September, nitrification accounted for the largest fraction of ammonium transformation, and the large reactive surface area of the marsh played a crucial role in nitrogen transformation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations